Strategic Planning as a Cornerstone of Quality Assurance in Higher Education: A Coupling Model with ISO 21001, ESG/ASG-QA, and Evidence Dashboards (British Journal of Multidisciplinary and Advanced Studies, 2026)
This paper argues that strategic planning is the engine of quality assurance (QA) in higher education when it is explicitly coupled with recognized reference frameworks and operational evidence infrastructures. Drawing on an integrative synthesis of the Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG), the African Standards and Guidelines for Quality Assurance (ASG‑QA), and ISO 21001:2018, we propose a “coupling model” that links mission and goals to process inventories, risk registers, and role‑based dashboards. We illustrate the model with the Cameroonian policy context namely the Education and Training Sector Strategy 2023–2030 (ETSS 2030) and the National Development Strategy 2020–2030 (NDS30) and with regional QA reforms (e.g., South Africa’s QAF). We show how institutional KPIs can be derived from sector targets and embedded in Plan‑Do‑Check‑Act (PDCA) cycles supported by an EMIS 2.0 architecture focused on learning and accountability. Recent research on learning‑analytics dashboards and human‑centered provides design considerations for usability, equity, and pedagogical actionability. The contribution is a practical mapping procedure and dashboard specification that translate high‑level QA requirements into auditable processes, data elements, and governance artifacts feasible for universities in resource‑constrained settings.